Maryland Community Colleges 1980 Program Evaluations - Maryland State Board for Community Colleges, Annapolis; Maryland State Board for Community Colleges, Annapolis ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
This report contains qualitative evaluations of 48 programs throughout the Maryland community college system, as well as a statewide evaluation of Teacher Education transfer programs. A summary of the Teacher Education programs is presented first, in which the purpose and role of teacher education in the community college, enrollment trends, student characteristics, and transfer patterns and problems are considered. The report then presents 48 program evaluations completed by individual colleges in response to questions relating to problems of low employment of or low awards for graduates, low enrollment, or high costs. In addition to the Teacher Education programs, the following programs are evaluated: Business Technology; Automotive Technology; Ocean Engineering Technology; International Trade; Piano Technology; Heating, Ventilation, and Refrigeration; Environmental Health Technology; Materials Management; Television Operations and Maintenance; Chemical Technology; Business Management; Horticulture; Recreation Leadership; Agricultural Business; Early Childhood Development; Special Education Instructional Aide; Banking; Engineering Technology; Public Administration Assistant; Secretarial Science; Environmental and Renewable Resources; Early Childhood Instructional Aide; Insurance; Interior Design; Retailing; Computer Technician; General Engineering; Criminal Justice; Human Services; General Studies; and Retail Management. (AYC)
ERIC Note: For a related document, see ED 181 967.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Articulation (Education); Community Colleges; Enrollment; Job Placement; Program Costs; Program Evaluation; State Surveys; Teacher Education Programs; Two Year Colleges; Vocational Education; Maryland; Reports, Evaluative